HUBUNGAN PENGETAHUAN DAN SIKAP IBU TENTANG GIZI DENGAN STATUS GIZI BALITA DI PUSKESMAS BANDAR KHALIPAH KEC. PERCUT SEI TUAN KAB. DELI SERDANG TAHUN 2019 - Astriana Fransiska Butarbutar; Lany Mutia (JURNAL KESMAS DAN GIZI (JKG), 2019)
Nutritional status is a state of status on a person's body that is related to food consumption, and is influenced by various internal and external factors such as age, sex, physical activity, illness, and socio-economic conditions. The purpose of this study was to determine the relationship between knowledge and attitudes with nutritional status of children in the Puskesmas Bandar Khalipah. The design of this study used a cross sectional design. The samples in the study were 50 respondents using random sampling techniques. Research analysis uses unvariate analysis and bivariate analysis. The results showed the relationship between maternal knowledge about nutrition and the nutritional status of children using the chi-square test obtained p value = 0.001 (p <Î±) where 0.001 <0.05 which means there is a relationship between maternal knowledge of nutrition and nutritional status of toddlers at Puskesmas Bandar Khalipah in 2019. The relationship between maternal attitudes about nutrition and the nutritional status of children using the chi-square test obtained a value of p = 0.002 (p < Î±) where 0.002 <0.05, which means there is a relationship between maternal attitudes about nutrition and the nutritional status of children at Puskesmas Bandar Khalipah in 2019. The results of this study can be suggested to be developed and broaden the horizons in the field of services and so on the basic data for the development of further research related to the Relationship between Knowledge and Attitudes of Mothers with Nutritional Status of Toddlers.